Thuggery of Liberation and Election in Kebbi State - Abdullahi, Danjuma; Baba, Yahaya T.; Musa, Aminu (International Journal of Social and Administrative Sciences, 2017)
Since the return of the Fourth Republic in Nigeria, thuggery has being the major issue of elections and electioneering campaign in Kebbi State. Previous studies mainly discussed the issue of thuggery and its effect on the Nigeria’s democratic system without touching on the thuggery of liberation. Thus, this research addresses thuggery of liberation and its effects on election in Kebbi State. Data were sourced through interviews conducted with the stake holders such as staff of the electoral institution, civil society, security agencies such as the Police, Nigerian Security and Civil Defence Corps as well as Nigerian Prisons Service and Nongovernmental Organizations such as Vigilante group. The findings revealed that liberation thuggery is a way of advancing community effort and development by making sure that members of that community participate in community development. The paper makes some recommendations on the way out.